please send me the procedure
Attachments:
![](https://hi-static.z-dn.net/files/dea/a49e48bf371d2ac007a847efe122cc3d.jpg)
Answers
Answered by
1
x=√ab
x^2=ab
y=√bc
y^2=bc
now
x^2+y^2=ab+bc. Equation(1)
=b(a+c)
SINCE a,b,c are in AP therefore
b=a+c/2
a+c=2b
putting above values in the equation 1
we get
=b*2b
=2b^2
Answer is option 3
HOPE IT HELPS
MARK AS BRAINLIEST
x^2=ab
y=√bc
y^2=bc
now
x^2+y^2=ab+bc. Equation(1)
=b(a+c)
SINCE a,b,c are in AP therefore
b=a+c/2
a+c=2b
putting above values in the equation 1
we get
=b*2b
=2b^2
Answer is option 3
HOPE IT HELPS
MARK AS BRAINLIEST
Anonymous286:
Mark as brainliest
Similar questions